Maternal Prepregnancy 5-Hydroxytryptamine Exposure Affects the Early Development of the Fetus - Han, Yu; Zhang, Meng; Duan, Jiahui; Li, Leyi; Du, Jinge; Cheng, Hui; Zhang, Sheng; Zhai, Yanhui; An, Xinglan; Li, Qi; Zhang, Xueming; Li, Ziyi; et al. (Frontiers in Physiology, 2022)
In recent decades, the increasing incidence of depression has contributed to an increase in the use of serotonergic drugs such as antidepressants, which predisposes humans to serotonin syndrome. Serotonin syndrome is caused by elevated serotonin levels in the central and peripheral nervous systems. It has been well documented that the development of offspring can be affected by maternal exposure to environmental challenges such as stress, diseases, or an unhealthy diet during pregnancy. Serotonin, also called 5-hydroxytryptamine (5-HT), is widely expressed in the female reproductive system and plays an important role in the development of follicles and embryos. However, whether the suffering of the mother from serotonin syndrome before pregnancy affects fetal development is still uncertain. In the present study, to explore the effect of maternal prepregnancy 5-HT exposure on the fetus, intraperitoneal injection of 5-HT was used to change maternal prepregnancy 5-HT levels. It was found that maternal prepregnancy 5-HT exposure significantly reduced the body weight and liver weight and the levels of estrogen and progesterone in female mice. Although there was no significant difference in the cleavage rate and blastocyst rate between the 5-HT and control groups, maternal prepregnancy 5-HT exposure increased the percentage of embryo resorption, decreased placental weight and led to placental inflammation at E13.5. Notably, 5-HT exposure caused weight loss in the offspring at 2 weeks. These results suggested that maternal prepregnancy 5-HT exposure could affect the development of the offspring, which was partly caused by reduced hormonal secretion and placental inflammation.